2020
DOI: 10.5194/bg-2020-133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonality, drivers, and isotopic composition of soil CO<sub>2</sub> fluxes from tropical forests of the Congo Basin

Abstract: Abstract. Soil respiration is an important carbon flux and key process determining the net ecosystem production of terrestrial ecosystems. To address the enormous lack of quantification and understanding of seasonality in soil respiration of tropical forests in the Congo Basin, soil CO2 fluxes and potential controlling factors were measured for the first time annually in two dominant forest types (lowland and montane) of the Congo Basin during three years at varying temporal resolution. Soil CO2 fluxes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This reinforces the idea that there is source limitation within events in the Miombo woodland, as no change in POM sources is visible throughout the whole rainy season and no shift of source material occurs between baseflow and storm flow conditions. In previous studies at the same sites, we reported the ranges of δ 13 C and C:N values from different potential source material within our catchments (Baumgartner et al, 2020(Baumgartner et al, , 2021. These ranges are plotted together with the values of sediment samples from this study (Fig.…”
Section: Sediment Sources and Transformationsmentioning
confidence: 78%
See 1 more Smart Citation
“…This reinforces the idea that there is source limitation within events in the Miombo woodland, as no change in POM sources is visible throughout the whole rainy season and no shift of source material occurs between baseflow and storm flow conditions. In previous studies at the same sites, we reported the ranges of δ 13 C and C:N values from different potential source material within our catchments (Baumgartner et al, 2020(Baumgartner et al, , 2021. These ranges are plotted together with the values of sediment samples from this study (Fig.…”
Section: Sediment Sources and Transformationsmentioning
confidence: 78%
“…1). Soils in the lowland forest are classified as deeply weathered Ferralsols (Van Ranst et al, 2010) with a loamy sand texture (Baumgartner et al, 2020). The catchment area has been estimated using the 30 m Shuttle Radar Topographic Mission (SRTM) derived digital elevation model (DEM, NASA JPL) and the GPS (GPSMAP 60CSx, Garmin, accuracy <5 m) coordinates of the flume position.…”
Section: Study Sitesmentioning
confidence: 99%
“…In recent years, our understanding of N cycling in the central Congo basin has increased substantially (Bauters et al 2016(Bauters et al , 2018Baumgartner et al 2020;Gallarotti et al 2021). From these studies we know that the forests of the Congo basin receive high atmospheric N deposition (Bauters et al 2018) but, at the same time, show relatively low rates of N 2 O emission (Gallarotti et al 2021).…”
Section: Introductionmentioning
confidence: 99%